2020
DOI: 10.5539/jel.v9n5p205
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fear of Missing Out (FoMO) Levels and Cyberloafing Behaviour of Teachers

Abstract: The purpose of this research was to investigate the relationship between teachers’ fear of missing out (FoMO) levels and their cyberloafing behaviour and to reveal whether teachers’ FoMO and their cyberloafing behaviour differ according to their gender. The sample of the research consisted of 702 secondary school teachers working in state schools within the borders of Istanbul in 2019-2020 education year. According to the research, it was identified that the level of teachers’ FoM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
(47 reference statements)
0
3
0
1
Order By: Relevance
“…The third finding of the study found a positive correlation between cyberloafing and FoMO. The literature contains similar studies, which reveal significantly positive correlations between cyberloafing and FoMO (Gullu & Serin, 2020;Tozkoparan & Kuzu, 2019). In addition to these studies, Senel et al (2019) applied the Cyberloafing Behavior Scale to 124 university students and asked why they showed these behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The third finding of the study found a positive correlation between cyberloafing and FoMO. The literature contains similar studies, which reveal significantly positive correlations between cyberloafing and FoMO (Gullu & Serin, 2020;Tozkoparan & Kuzu, 2019). In addition to these studies, Senel et al (2019) applied the Cyberloafing Behavior Scale to 124 university students and asked why they showed these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion of this study points to FoMO in terms of the "Curiosity" subdimension. One study including 702 teachers examined the existence of the relationship between FoMO and cyberloafing and it found a highly significantly positive relationship between FoMO and cyberloafing (Gullu & Serin, 2020). In another study conducted among 141 teacher candidates, a significant correlation between the FoMO levels of teacher candidates and their cyberloafing behaviors was established and it was found that FoMO was a significant precursor to cyberloafing behavior in terms of socialization.…”
Section: Introductionmentioning
confidence: 99%
“…Öğrencilerin FomO davranışları ile sanal kaytarma davranışları arasındaki ilişkiyi inceleyen iki çalışmada (Tozkoparan & Kuzu, 2019;Ergin & Karataş, 2022) ilişki düzeyinin pozitif ve anlamlı çıktığı ifade edilmiştir. Benzer şekilde örneklem olarak öğretmenleri temel alan ve aynı ilişkiselliği inceleyen Güllü & Serin (2020)'in çalışmasında da pozitif ve anlamlı bir ilişki tespit edilmiştir. Fakat FoMO ile akademik performans algısında olduğu gibi literatürde akademisyenler özelinde FoMO davranışı ve sanal kaytarma davranışı ilişkisini inceleyen herhangi bir çalışmaya rastlanılmamıştır.…”
Section: Tartışma Ve Sonuçunclassified
“…As a result, teachers may consciously or unintentionally engage in psychological withdrawal behaviors such as dealing with personal affairs at school, cyberloafing, silence, and slacking. What's more fearing of missing out has also teachers withdraw from work by cyberloafing (Gullu & Serin, 2020). In short, this situation may have a detrimental impact on the effectiveness of the school and teacher performance.…”
Section: Introductionmentioning
confidence: 99%